Às margens do Tocantins: memórias de professores aposentados em Miracema – TO (1960-1990) - Barros, Aragoneide Martins (Universidade Federal do Tocantins, 2023)
The purpose of this paper is to narrate the memories of retired teachers who worked from 1960 to 1990 at Tocantins School (CT), at José Damasceno Vasconcelos School and at Santa Terezinha High School Teaching Center (CEMST), in the city of Miracema do Norte. Among the specific objectives, it was sought to identify and interview retired teachers who worked in the educational institutions mentioned above, to bring up the motivations for the exercise of teaching in a limited educational setting and with reduced teacher training. The analysis of the teachers' memories revealed various aspects of the daily life of elementary schools in the north of Goiás: teaching methods, school rules and regulations, and the routine experienced by students and teachers. In the bibliographic research, the authors, who deal with Brazilian teaching history, were studied are the following: Aranha (1996) Nunes (2002), Vidal (2005), Veiga (2007), Saviani (2007), Faria Filho (2000), Ribeiro (1998) Ribeiro (1998), among others. The research was based on the meaning of educational institutions by Noselha (2009), Sanfelice (2007) and Justino Magalhães (2004), which in the book “Weaving nexuses: history of educational institutions” emphasizes educational institutions as spaces for the transformation of the individual, which brings a sociocultural burden, from the discussion education / action, information from the cultural and social context to the epistemological; education / content, which is the epistemological knowledge itself, and education / product, the result of the educational process. The methodology of oral history was applied, adopting concepts from Verena Alberti (2000), Bosi (1994), Halbawachs (2003), Michael Pollak (1992), Portelli (2006), Meihy and Holanda (2010) and others. The analysis of the interviews was based on Bardin (2011) and Jacques Le Goff (1998). All interviews were transcribed and examined in order to analyze the official history recorded in the school documents and the story narrated in the interviews of the investigated subjects. The interviews followed the procedures provided for the identification of witnesses, construction of a questionnaire, consent form with explanation and analysis of the statements. The documents used were: Political Pedagogical Projects, Internal Regulations, photographs of the school unit, newspaper clippings from the old north of Goiás about the school, the city, and the collection of private individuals. The use of oral history as an investigation method allowed subjects, institutions and school movements to raise a new perspective on the educational scenario in northern Goiás. The interviewees highlighted places, events, characters, educational practices, and produced information about the culture, rites and daily life of the school, in a local / national context of Brazilian education in the 1960s and 1990s.